EL USO DE LA TRADUCCIÓN EN EL APRENDIZAJE DE UNA LENGUA EXTRANJERA: EL CASO DE LOS PRONOMBRES CLÍTICOS EN ESPAÑOL. - Escutia, Marciano (Atlantis (0210-6124), 2005)
The rejection of the use of translation in class has been taken for granted in the last two decades as the correct and accepted view on the teaching of foreign languages. The reasons behind it are presented in this paper as well as an analysis of the role of translation in adult foreign language acquisition. It is also suggested that the lack of good structural translations can lead to establishing wrong syntactic specifications about particular structures of the target language and, probably, to the delay in their acquisition by adults. This is exemplified here for the case of the foreign language learning of Spanish pronominal clitics. In addition, several didactic strategies are proposed to circumvent some of the learning problems posed by the latter.